Post-embryonic Development of Intramandibular Glands in Pachycondyla verenae (Forel) (Hymenoptera: Formicidae) workers - Luiza CB Martins; Jacques HC Delabie; Jose C Zanuncio; José Eduardo Serrão (Sociobiology)
The current knowledge of intramandibular glands in Hymenoptera is focused on occurrence and morphology in adult insects. This is the first report regarding the post-embryonic development of intramandibular glands in a “primitive” ant, Pachycondyla verenae. In this study, we analyzed mandibles of prepupae, white-eyed, pink-eyed and black-eyed pupae, pupa of pigmented body pupae, and adults. Adult workers of P. verenae have intramandibular glands with epidermal secretory cells of class I and isolated glands of class III, and both glands have onset differentiation in pink-eyed pupae. Some histological sections were submitted to histochemical test for total proteins and neutral polysaccharides. Histochemical tests showed occurrence of polysaccharides and proteins in epidermal secretory cells of class I from the white-eyed pupae, polysaccharides and proteins in pink-eyed pupae to black-eyed pupae in both glands classes I and III and presence of polysaccharides in adult ants also in both gland classes I and III. Intramandibular glands of classes I and III in P. verenae workers differentiate during pupation, with onset occurring in pink-eyed pupae, and completion occurring in black-eyed pupae.